Dissolved iron release by sediment and dust particles in Antarctic seawater greater than glacial flour and sea-ice particles - Matthew Corkill; Klaus Martin Meiners; Pat Wongpan; Pier van der Merwe; Layla Creac'h; Sandrin Feig; Talitha Nelson; Abigail Jessica Rose Smith; Ashley T. Townsend; Samantha Twiname; Delphine Lannuzel (Marine Chemistry, 2025)

Plant performance responds to intraspecific variation in soil inocula from individual Solidago clones - Bryan S. Foster; Brendan B. Haile; Justin T. Campnell; Thomas Canam; Marci J. Gallagher; Scott J. Meiners (Plant Ecology, 2022)

Discovery pipelines for marine resources: an ocean of opportunity for biotechnology? - D. Smith; A. G. Buddie; R. J. M. Goss; J. Overmann; C. Lepleux; M. Brönstrup; B. Kloareg; T. Meiners; P. Brennecke; A. Ianora; F.-Y. Bouget; P. Gribbon; et al. (World Journal of Microbiology and Biotechnology, 2019)

Competition and coexistence in plant communities: intraspecific competition is stronger than interspecific competition - Peter B. Adler; Danielle Smull; Karen H. Beard; Ryan T. Choi; Tucker Furniss; Andrew Kulmatiski; Joan M. Meiners; Andrew T. Tredennick; Kari E. Veblen (Ecology Letters, 2018)
Theory predicts that intraspecific competition should be stronger than interspecific competition for any pair of stably coexisting species, yet previous literature reviews found little support for this pattern. We screened over 5400 publications and identified 39 studies that quantified phenomenological intraspecific and interspecific interactions in terrestrial plant communities. Of the 67% of species pairs in which both intra‐ and interspecific effects were negative (competitive), intraspecific competition was, on average, four to five‐fold stronger than interspecific competition. Of the remaining pairs, 93% featured intraspecific competition and interspecific facilitation, a situation that stabilises coexistence. The difference between intra‐ and interspecific effects tended to be larger in observational than experimental data sets, in field than greenhouse studies, and in studies that quantified population growth over the full life cycle rather than single fitness components. Our results imply that processes promoting stable coexistence at local scales are common and consequential across terrestrial plant communities.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Beyond biodiversity: individualistic controls of invasion in a self‐assembled community - Scott J. Meiners; Mary L. Cadenasso; Steward T. A. Pickett (Ecology Letters, 2004)
Recent experimental and simulation results, and competition‐based ecological theory, predict a simple relationship between species richness and the invasibility of communities at small spatial scales – likelihood of invasion decreases with increasing richness. Here we show data from 42 continuous years of sampling old field succession that reveal quite different dynamics of plant invasion. Contrary to experimental studies, when richness was important in explaining invasion probability, it was typically positively associated with species invasion. Invasion of several species had a unimodal response to resident species richness, which appeared to be a mixture of compositional influences and a richness effect. Interestingly, invasions by native and exotic species did not fundamentally differ. Control of species invasion in this system is individualistic, caused by a variety of community‐level mechanisms rather than a single prevailing richness effect.